La disfunción familiar en el rendimiento académico de los niños de sexto año de educación general básica, paralelo “b” de la escuela de educación básica “Martiniano Guerrero Freire” Riobamba, período 2017- 2018. - Zambrano Basurto, Nataly Andreina (2018)
The objective of this research work is to determine the relationship between family dysfunction and academic performance, which showed that family disintegration affects the educational process. The dysfunctional family parents do not have an adequate behavior to establish a development considered normal on the family according to Hunt (2007) and academic performance is understood by Pizarro (1985) as a measure of the respondent or indicative capacities that manifest, in an estimated way, what a person has leaned as a result of a training process. To verify this research, a qualitative approach with a diagnostic design (correlational) was carried out through observation and the survey with its instruments, the observation form and the questionnaire applied to 36 students and 36 parents. It is concluded that there is a significant relationship between family dysfunction and the academic performance of children, the harmony of the home is essential and as an effect the safety of relating with classmates and following the rules established in the school.